2019
DOI: 10.1080/09540261.2019.1664421
|View full text |Cite
|
Sign up to set email alerts
|

The role of mood, post-traumatic stress, post-concussive symptoms and coping on outcome after MTBI in elderly patients

Abstract: To cite this article: Amaal Eman Abdulle & Joukje van der Naalt (2020) The role of mood, posttraumatic stress, post-concussive symptoms and coping on outcome after MTBI in elderly patients,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The eight adult studies that centered on symptoms of depression utilized the adapted version of the Composite International Diagnostic Interview Screening Scales ( 61 , 88 ), qualitative interviews ( 62 , 81 ), the British Columbia Major Depression Inventory, 2nd Edition ( 63 , 82 ), the Center for Epidemiological Studies Depression Scale ( 64 , 83 ), the Beck Depression Inventory ( 65 , 66 , 68 , 94 ), or the General Health Questionnaire ( 67 , 84 ). Between the nine adult studies on combined symptoms of anxiety and depression, four used the Hospital Anxiety and Depression Scale ( 70 , 72 , 75 , 76 , 93 ), while others used the Impact of Event Scale ( 69 , 95 ), the Rivermead Post-Concussion Symptoms Questionnaire ( 69 , 96 ), Depression and Anxiety Stress Scales-42 ( 71 , 85 ), the Beck Anxiety Inventory ( 73 , 86 ) and Beck Depression Inventory ( 73 , 94 ), interviews with symptoms according to DSM-IV criteria ( 74 , 87 ), and the Glasgow Outcome Scale -Extended ( 77 , 97 ). Finally, the two adult studies that included “other” mental health outcomes, included the Impact of Event Scale ( 69 , 95 ) and qualitative interviews ( 62 , 81 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The eight adult studies that centered on symptoms of depression utilized the adapted version of the Composite International Diagnostic Interview Screening Scales ( 61 , 88 ), qualitative interviews ( 62 , 81 ), the British Columbia Major Depression Inventory, 2nd Edition ( 63 , 82 ), the Center for Epidemiological Studies Depression Scale ( 64 , 83 ), the Beck Depression Inventory ( 65 , 66 , 68 , 94 ), or the General Health Questionnaire ( 67 , 84 ). Between the nine adult studies on combined symptoms of anxiety and depression, four used the Hospital Anxiety and Depression Scale ( 70 , 72 , 75 , 76 , 93 ), while others used the Impact of Event Scale ( 69 , 95 ), the Rivermead Post-Concussion Symptoms Questionnaire ( 69 , 96 ), Depression and Anxiety Stress Scales-42 ( 71 , 85 ), the Beck Anxiety Inventory ( 73 , 86 ) and Beck Depression Inventory ( 73 , 94 ), interviews with symptoms according to DSM-IV criteria ( 74 , 87 ), and the Glasgow Outcome Scale -Extended ( 77 , 97 ). Finally, the two adult studies that included “other” mental health outcomes, included the Impact of Event Scale ( 69 , 95 ) and qualitative interviews ( 62 , 81 ).…”
Section: Resultsmentioning
confidence: 99%
“…For each of these studies, the severity of both depression and anxiety was measured. There were five studies that reported a higher prevalence of anxiety and depression symptoms in patients who develop PPCS ( 69 , 71 , 72 , 74 , 75 ). Four studies did not find a significant difference in both outcomes ( 69 , 73 , 77 , 98 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCS for this same sample was also examined (Abdulle et al, 2020) using the Head Injury Symptoms Checklist (HISC) and measures of posttraumatic stress and coping. Results indicated that 73% of older people endorsed at least one PCS 2 weeks after injury, with the most frequent complaints being dizziness, fatigue, and headache.…”
Section: Hume-mtbi Outcome In Older Peoplementioning
confidence: 99%
“…Five studies reported the proportion of "complete" recovery for older adults using the GOS/GOSE; four examined outcome at 6-month post-injury, whereas one study (Deb et al, 1998) observed outcome at 1-year post-injury. The paper by Abdulle & van der Naalt (2020) was initially identified for inclusion; however, as this study dichotomised older age as ≥60 years and all other studies defined older age as ≥65 years, the van der Naalt et al ( 2017) data, which shared the same sample as Abdulle et al (2018Abdulle et al ( , 2020 and reported proportion of recovery based on age ≥65 years, was used in preference. This also provided data for a further subgroup analysis (old vs. young), as two other studies reported proportion of recovery for younger adults aged between 18 and 64 years as well as their older age samples.…”
Section: Life Participationmentioning
confidence: 99%